2003
DOI: 10.1128/jvi.77.24.13225-13231.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanismof Action and Antiviral Activity of Benzimidazole-Based AllostericInhibitors of the Hepatitis C Virus RNA-Dependent RNAPolymerase

Abstract: The RNA-dependent RNA polymerase of hepatitis C virus (HCV) is the catalytic subunit of the viral RNA amplification machinery and is an appealing target for the development of new therapeutic agents against HCV infection. Nonnucleoside inhibitors based on a benzimidazole scaffold have been recently reported. Compounds of this class are efficient inhibitors of HCV RNA replication in cell culture, thus providing attractive candidates for further development. Here we report the detailed analysis of the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
216
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(228 citation statements)
references
References 29 publications
11
216
1
Order By: Relevance
“…These results confirm that BMS-791325, like the previous thumb site 1 inhibitors tested, has no impact on elongation (16,18). The inhibition in systems that model elongation suggests that BMS-791325 blocks a step before the incorporation of nucleotides.…”
Section: Assaysupporting
confidence: 77%
See 2 more Smart Citations
“…These results confirm that BMS-791325, like the previous thumb site 1 inhibitors tested, has no impact on elongation (16,18). The inhibition in systems that model elongation suggests that BMS-791325 blocks a step before the incorporation of nucleotides.…”
Section: Assaysupporting
confidence: 77%
“…Mode of Inhibition-Previous reports showed that compounds binding at thumb site 1 inhibit the initiation of RNA replication (16,18) and not elongation; however, BMS-791325 appears to be 5-75 times more potent than previously studied compounds and inhibits equally in model systems of de novo and primer-dependent synthesis. Because two of the four replication systems are assumed to model elongation (poly(A)⅐dT 12 and HCV RNA), a trapping experiment was performed to confirm that BMS-791325 has no impact on the elongation phase of replication.…”
Section: Potent and Specific Inhibition Of Hcv Ns5b Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…Activity after hybridization to the DNA strand used in single molecule experiments was tested using the R (lanes 4 and 8). Lanes 2,4,10,12,14, and 16 show full-length products in addition to shorter products representing pausing sites. Lanes 6 and 8 show a truncated product.…”
Section: Ns5b Mutations Along the Rna Binding Channel Lead To Reducedmentioning
confidence: 99%
“…Thumb pocket 1 non-nucleoside inhibitors (NNIs) or finger loop NNIs bind to a region of the thumb that is otherwise occupied by the flexible ⌬1 finger loop, which seems to impede productive RNA binding (Fig. 1b) (11)(12)(13)(14).…”
Section: The Hepatitis C Virus (Hcv)mentioning
confidence: 99%